Medium-chain acyl-CoA dehydrogenase deficiency: Two novel ACADM mutations identified in a retrospective screening. Issue 4 (April 2018) - Smon, Andraz; Groselj, Urh; Debeljak, Marusa; Zerjav Tansek, Mojca; Bertok, Sara; Avbelj Stefanija, Magdalena; Trebusak Podkrajsek, Katarina; Battelino, Tadej; Repic Lampret, Barbka
Objective: The aim of this study was to determine whether an expanded newborn screening programme, which is not yet available in Slovenia, would have detected the first two patients with medium-chain acyl-CoA dehydrogenase (MCAD) deficiency in the country. Two novel ACADM mutations are also described. Methods: Both patients were diagnosed clinically; follow-up involved analysis of organic acids in urine, acylcarnitines in dried blood spots, and genetic analysis of ACADM . Cut-off values of acylcarnitines in newborns were established using analysis of 10, 000 newborns in a pilot screening study. Results: In both patients, analysis of the organic acids in urine showed a possible β-oxidation defect, while the specific elevation of acylcarnitines confirmed MCAD deficiency. Subsequent genetic analysis confirmed the diagnosis; both patients were compound heterozygotes, each with one novel mutation (c.861 + 2T > C and c.527_533del). The results from a retrospective analysis of newborn screening cards clearly showed major elevations of MCAD-specific acylcarnitines in the patients. Conclusions: An expanded newborn screening programme would be beneficial because it would have detected MCAD deficiency in both patients before the development of clinical signs. Our study also provides one of the first descriptions of ACADM mutations in Southeast Europe.